Chemical composition and larvicidal activity of edible plant-derived essential oils against the pyrethroid-susceptible and -resistant strains of Aedes aegypti (Diptera: Culicidae) - Nataya Sutthanont (2018)
The chemical compositions and larvicidal potential against mosquito vectors of selected essential oils obtained from five edible plants were investigated in this study. Using a GC/MS, 24, 17, 20, 21, and 12 compounds were determined from essential oils of Citrus hystrix, Citrus reticulata, Zingiber zerumbet, Kaempferia galanga, and Syzygium aromaticum, respectively. The principal constituents found in peel oil of C. hystrix were β-pinene (22.54%) and d-limonene (22.03%), followed by terpinene-4-ol (17.37%). Compounds in C. reticulata peel oil consisted mostly of d-limonene (62.39%) and γ-terpinene (14.06%). The oils obtained from Z. zerumbet rhizome had α-humulene (31.93%) and zerumbone (31.67%) as major components. The most abundant compounds in K. galanga rhizome oil were 2-propeonic acid (35.54%), pentadecane (26.08%), and ethyl-p-methoxycinnamate (25.96%). The main component of S. aromaticum bud oil was eugenol (77.37%), with minor amounts of trans-caryophyllene (13.66%). Assessment of larvicidal efficacy demonstrated that all essential oils were toxic against both pyrethroid-susceptible and resistant Ae. aegypti laboratory strains at LC50, LC95, and LC99 levels. In conclusion, we have documented the promising larvicidal potential of essential oils from edible herbs, which could be considered as a potentially alternative source for developing novel larvicides to be used in controlling vectors of mosquitoborne disease.